Neural Network of Multivariate Square Rational Bernstein Operators - Mohammad, Ibtihal J.; Mohammad, Ali J. (Communications in Mathematics and Applications, 2022)
This paper introduced a family of neural networks of multivariate square rational Bernstein operators defined by extending the artificial neural networks multivariate Bernstein by using square Bernstein polynomials and studied the behavior of this neural network. Also, gave application through some numerical examples.